Comments on Maria Panum Baastrup’s Invitation systems and identification in Late Iron Age southern Scandinavia - Watt, Margrethe (Danish Journal of Archaeology, 2016)
The article provides some basic facts and updates on the gold foil figures and also questions certain aspects of Baastrups interpretation. Attention is drawn to the importance of the complex iconographic content of the gold foils.